ANALISIS RENCANA ANGGARAN PENDAPATAN DAN BELANJA TERHADAP LAPORAN REALISASI ANGGARAN BERBASIS KINERJA BADAN LAYANAN UMUM DAERAH TAHUN ANGGARAN 2015-2018 (Studi Kasus Rumah Sakit Umum Daerah Depati Hamzah) - Halawa, Selfia; Panjaitan, Fery; Ahmad Agin, Arka'a (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
Thesis entitled "Analysis of the Revenue and Expenditure Budget Plan Against the Report of Budget Realization Based on the Performance of the Regional Public Service Agency for the 2015-2018 Fiscal Year (Case Study of the Regional Public Hospital Depati Hamzah)" on behalf of Selfia Halawa. Under the guidance of Supervisor I Mr fery panjaitan, SE, MM and Supervisor II Mr Arka’a Ahmad Agin, Ss, M.Sc. Depati Hamzah BLUD is a management right granted to RSU owned by Pangkal Pinang municipal government whose budget management is sourced directly from Pangkal Pinang regional regional budget. This study aims to assess the performance of the expenditure budget during the budget period. The performance evaluation of the expenditure budget is known after the use and absorption of the budget itself in activities that exist at the agency. The budget performance can be concluded effectively after passing a series of criteria based on descriptive qualitative analysis used in research. The research uses data collection techniques in the form of documentation and direct interviews with related parties. The analytical method used is a descriptive method based on the revenue and expenditure budget plan in the budget realization report, using a comparison between the revenue and realization budget plan, expenditure and realization budget, revenue and expenditure budget against the realization report. The results of the analysis are based on a comparison between the planned revenue budget and the relation in 2015 where revenue realization increased by 108.94%, meaning that the performance of the Depati Hamzah Regional Hospital in 2015 was very effective. Depati Hamzah's Regional General Hospital revenue in 2016-2017 is less effective. Where the revenue budget in 2016 decreased by 80.98% and the income budget in 2017 decreased by 77.09%. While the budget of the Depati Hamzah Regional General Hospital Revenue in 2018 has decreased with an achievement level of 65.14%, meaning that the performance of the Depati Hamzah Regional Public Hospital in PangkalPinang in 2018 is very bad / ineffective. Based on a comparison between the planned budget and the realization of the 2015-2018 Regional Public Houses Depati Hamzah has made efficient budget savings.While the results of the analysis of the revenue and expenditure budget in 2015, performance-based budget management has been carried out effectively, namely where the budget in 2015 got a surplus of 3,483,883,008.95, while in 2016-2018 experienced consecutive deficits. Where the income and expenditure budget in 2016 was a deficit of (1,251,400,332.80) and in 2017 a deficit of 2017 while in 2018 a deficit of (531,499,835.22). This shows that the performance of the depati hamzah public hospital is decreasing.